Direct detection of a dioxygen adduct of cytochrome a3 in the mixed valence cytochrome oxidase/dioxygen reaction - Woodruff, William; Babcock, Gerald; Varotsis, Constantinos (My University, 1990)
Time-resolved resonance Raman spectra have been recorded during the reaction of mixed valence (a3+ a32+) cytochrome oxidase with dioxygen at room temperature. In the spectrum recorded at 10 μs subsequent to carbon monoxide photolysis, a mode is observed at 572 cm-1 that shifts to 548 cm-1 when the experiment is repeated with 18O2. The appearance of this mode is dependent upon the laser intensity used and disappears at higher incident energies. The high frequency data in conjunction with the mid-frequency data allow us to assign the 572 cm-1 mode to the Fe-O stretching vibration of the low-spin O2 adduct that forms in the mixed valence cytochrome oxidase/dioxygen reaction. The 572 cm-1 ν(Fe2+-O2) frequency in the mixed valence enzyme/O2 adduct is essentially identical to the 571 cm-1 frequency was measured for this mode during the reduction of O2 by the fully reduced enzyme (Varotsis, C., Woodruff, W.H., and Babcock, G.T. (1989) J. Am. Chem. Soc. 111, 6439-6440; Varotsis, C., Woodruff, W.H., and Babcock, G.T. (1990) J. Am. Chem. Soc. 112, 1297), which indicates that the O2-bound cytochrome a3 site is independent of the redox state of the cytochrome a/Cu(A) pair. The photolabile oxy intermediate is replaced by photostable low- or intermediate-spin cytochrome a33+, with t( 1/2 ) ~ 200 μs
Keywords: Cytochrome oxidase; Oxygen; Raman spectroscopy; Carbon monoxide; Chemistry; Photochemistry; Cattle